COVID-19 insolvency moratoria, firm selection, and allocative efficiency - Rahali, Mahdi

Querying Interval-Based Temporal Data with SPARQL - Corman, Julien; Kontchakov, Roman; Okulmus, Cem (Proceedings of the 33rd International Symposium on Temporal Representation and Reasoning (TIME 2026))

Reaching for the Stars in EL Concept Learning - Gortworst, Bente; Okulmus, Cem; Ortiz, Magdalena; Turhan, Anni-Yasmin (Proceedings of the 39th International Workshop on Description Logics (DL 2026))

Scaling Bottom-Up IFDS Taint Analysis with Optimized Data-Flow Encoding - Schiebel, Fabian Benedikt; Bodden, Eric (40th European Conference on Object-Oriented Programming (ECOOP 2026))

Characterisation of Internal Periodic Structures in Additively Manufactured Components Using Guided Acoustic Waves - Wippermann, Mareen; Rickert, Marlene Ingeborg; Gebauer, Finn; Zeipert, Henning; Claes, Leander

Phononische Kristallographie mittels geführter akustischer Wellen - Wippermann, Mareen; Rickert, Marlene Ingeborg; Gebauer, Finn

Backreaction of stimulated Hawking radiation in an optical analogue - Procopio Peña, Lorenzo Manuel; Aguero-Santacruz, Raul; Bermudez, David; Leonhardt, Ulf (Nature)

Neue Perspektiven auf Verstetigung und Nachhaltigkeit im Kontext der Transfergestaltung in Innovationsprogrammen - Daniel-Söltenfuß, Desiree (Zeitschrift für Berufs- und Wirtschaftspädagogik)

Mechanochemical Near‐Ambient Synthesis of C 2 N Materials From HAT‐CN and its Precursors - Dippner, Pascal; Grätz, Sven; Lins, Jonas; Gutmann, Torsten; Borchardt, Lars (ChemSusChem)
C 2 N‐type carbon materials are typically obtained through high‐temperature treatment of nitrogen‐rich molecular precursors under inert atmosphere. Herein, we demonstrate mechanochemical approaches that enable the synthesis of C 2 N materials, namely by (i) the conversion of hexaazatriphenylenehexacarbonitrile (HAT‐CN) and by (ii) a one‐pot route starting from its molecular precursors, hexaketocyclohexane, and diaminomaleonitrile. Compared with conventional pyrolytic methods, mechanochemical approaches afford higher yields while significantly reducing energy input, thereby improving overall sustainability. The results highlight the decisive role of mechanical energy in directing carbon–nitrogen framework formation and demonstrate mechanochemistry as a versatile alternative to thermal routes for C 2 N synthesis.

Conscious Artificial Intelligence in Service - Breidbach, Christoph; Lars-Erik, Casper Ferm; Maglio, Paul; Beverungen, Daniel; Wirtz, Jochen; Twigg, Alex (Journal of Service Management)
Purpose: The purpose of this study is to identify, analyze, and explain the implications that could arise for service settings if AI systems develop, or are perceived to develop, consciousness – the ability to acknowledge their own existence and the capacity for positive or negative experiences. Design/methodology/approach: This study proposes and explores four hypothetical scenarios in which conscious AI in service could manifest. We contextualize our resulting typology in the health service context and integrate extant literature on technology-enabled service, AI consciousness, and AI ethics into the narrative. Findings: This study provides a unique theoretical contribution to service research in the form of a Type IV theory. It enables future service researchers to apprehend, explain, and predict how functionally conscious AI in service might unfold. Originality: An increasingly prolific public discourse acknowledges that conscious AI systems may emerge. Against this backdrop, this study aims to systematically explore a question that is perhaps the most critical and timely, but also inherently speculative, in relation to AI in service research by introducing much-needed theory and terminology. Practical implications: The ethical use of conscious AI in service could emerge as a distinct competitive advantage in the future. Achieving this outcome involves speculative yet actionable recommendations that include training, guiding, and controlling how humans engage with such systems, developing appropriate wellbeing protocols for functionally conscious AI systems, and establishing AI rights and governance frameworks.
Keywords: AI; AI consciousness; AI ethics; service systems

Epistemic Programming as a Scientific Field: Building a Community of Practice and an Interaction-Based Framework - Hüsing, Sven; Musaeus, Line Have; Caspersen, Michael E.; Schulte, Carsten; Barendsen, Erik; Grgurina, Nataša; Hauswirth, Matthias; Lonati, Violetta; Mani, Murali; Monga, Mattia; Nobles, Heidi; Reckinger, Scott; et al. (Proceedings of the 31st ACM Conference on Innovation and Technology in Computer Science Education V. 2)

On the association scheme of perfect matchings and their designs - Klawuhn, Lukas-André Dominik; Bamberg, John (Algebraic Combinatorics)
We investigate generalisations of 1-factorisations and hyperfactorisations of the complete graph $K_{2n}$. We show that they are special subsets of the association scheme obtained from the Gelfand pair $(S_{2n},S_2 \wr S_n)$. This unifies and extends results by Cameron (1976) and gives rise to new existence and non-existence results. Our methods involve working in the group algebra $\mathbb{C}[S_{2n}]$ and using the representation theory of $S_{2n}$.

Cross-Reality Context Awareness - Krings, Sarah Claudia (Lecture Notes in Computer Science)

Multimodalität in Erklärvideos: Strategien von Lernenden zur auditiven und visuellen Gestaltung globaler Gliederungen - Risse, Sylvia (Potenziale mündlicher Kommunikation im (Deutsch-)Unterricht – quer durch die Kompetenzbereiche)

Visualisierung von Schallausbreitungsphänomenen mittels Schlierentechnik - Dören, Karl; Hetkämper, Tim

Effiziente Simulation nichtlinearer, elastodynamischer Prozesse - Hölscher, Jonas

Ferne Exklaven, große Gefahr: Die Folgen dänischer Ansprüche auf die Herrschaft Jever für das Reich und die Spanischen Niederlande (1677–1686) - Huybrechts, Yves (Verhandeln und Repräsentieren in der Frühen Neuzeit: Europa, Reich, Region. Festschrift für Christoph Kampmann zum 65. Geburtstag)

A n j a v a n d e Po l -Te g g e : Belgische Literaturen in deutscher Übersetzung. Kulturelle und historische Verflechtungen von 1945 bis zur Gegenwart. Bielefeld: Transcript 2023 (Interkulturalität. Studien zu Sprache, Literatur und Gesellschaft, 25) - Huybrechts, Yves (Archiv für das Studium der neueren Sprachen und Literaturen)

Simon Watteyne, Lever l’impôt en Belgique. Une histoire de combats politiques (1830–1962). Brüssel, CRISP 2023 - Huybrechts, Yves (Historische Zeitschrift)

The impact of market power on banks' ESG scores - evidence from Europe and North America - Voigt, Simone; Uhde, André
This paper empirically examines the relationship between market power and Environmental, Social, and Governance (ESG) scores of banks in Europe and North America from 2010 to 2021, focusing separately on loan and deposit markets. Employing the Lerner Index as a non-structural measure of market power, our findings suggest that the impact of banking market power on ESG scores varies by region and the respective loan or deposit market. We find a negative effect of loan and deposit market power on ESG scores of European banks whereas the opposite effect can be observed for North American banks exhibiting loan market power. Further sensitivity analyses reveal that factors such as banks being Global Systemically Important (G-SIBs), and different ESG-related events like the Paris Agreement, the reemergence of the #MeToo movement and the COVID-19 pandemic may also explain the relationship between bank market power and ESG scores. Overall, our results underline that banking market power plays a pivotal role in enforcing ESG commitments in banking, offering key insights for policymakers, regulators, and banking stakeholders.
Keywords: Market Power; ESG scores; European and North American banking markets